Assessing the Knowledge of Patients with Atrial Fibrillation Using Oral Anticoagulants Medications - Alaa Kadhim Abdul-Hameed, Rajaa Ibrahim Abd, Ammar Salman Handel (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To evaluate patients’ knowledge about atrial fibrillation (AF) and anticoagulants as well as to find out a relationship between the level of patients’ knowledge and sociodemographic variables. Methodology: A descriptive cross-sectional study was performed on patients with atrial fibrillation aged more than 18 years. The study started on October 13th, 2021, to April 25th, 2022. The sample consists of 90 AF patients on oral anticoagulants who were admitted at Al-Nasiriya Heart Center in Thi-Qar City. Jessa Atrial Fibrillation Knowledge Questionnaire (JAKQ) was used for the collection of data after getting written approval from its author. Results: Only 6 out of 90 patients had good knowledge of AF, with a significant relationship between the level of patients’ knowledge and their socio-demographic characteristics such as age, level of education, and occupation. Conclusion: 62.2% of patients exhibited poor knowledge about AF. Patients who were aged less than 30, those with high education, and those who were employers demonstrated improved knowledge than other patients.